TRANSFORMATION OF TRADE FLOWS BETWEEN THE EU AND UKRAINE IN THE CONDITIONS OF INCREASING SECURITY RISKS - LYZUN, Mariia; VITÁLIŠOVÁ, Katarína; BORSEKOVÁ, Kamila (Journal of European Economy, 2024)
The EU is currently Ukraine’s largest trading partner. The European market is characterized by high solvency and capacity, which creates many opportunities for Ukrainian exporters. The article examines the transformation of trade flows between the European Union and Ukraine in the context of increased security risks caused by Russia’s full-scale military aggression against Ukraine. An analysis of the main changes in the structure of Ukraine’s foreign trade was carried out, including the reorientation of export and import flows to EU markets. A significant unevenness in the concentration of Ukrainian exports to EU countries was re vealed, which makes its economy more vulnerable to external shocks and points to the available opportunities for increasing exports to other EU member states. An assessment of the economic benefits and challenges faced by both sides was carried out. On the basis of the conducted SWOT analysis, opportunities for trade cooperation between the EU and Ukraine in the conditions of transformation of trade flows were identified. JEL: F13, F18, F52, O52.